Failure analysis of laminated composite plate under hygro-thermo mechanical load and optimisation - Choudhury, Arnab; Sarkar, Susenjit; Mondal, Samar Chandra (Zielona Góra: Uniwersytet Zielonogórski)
Failure analysis of laminated composite plates for different mechanical, thermo mechanical and hygro-thermo mechanical loads for different ply thicknesses, stacking sequences, fiber orientation angles and composite material systems is presented in the paper. A comparative study of different failure theories is also presented in the paper.
Keywords: first ply failure load; last ply failure load; strength ratio; fiber orientation angle; hybrid composite